Comparing Voice Related Quality of Life scores between fenestrated and speaking valve cannula users - Yanti, Lisa Apri; Dewi, Veni Rosita; Bahar, Erial (Oto Rhino Laryngologica Indonesiana, 2023)
Background: Tracheostomy is a procedure that aims to maintain the airway so that air can enter the lungs and bypass the upper airway. Tracheostomy causes physiological changes, especially in terms of communication, which leads to reduced voice-related quality of life. Fenestrated tracheal cannula and speaking valve can assist patients in generating voice. Objective: To compare the V-RQOL scores of the fenestrated tracheal cannula and speaking valve users. Methods: Analytic observational study using a cross-sectional design. Data collection was done through interviews with the V-RQOL questionnaire guide. The study was conducted in September-December 2022 at the THTBKL Polyclinic of Dr. Mohammad Hoesin Hospital Palembang. Data were analyzed with IBM SPSS 26. Results: 42 patients were using tracheal cannula, with 21 patients each with a fenestrated and speaking valve tracheal cannula. Patients with fenestrated tracheal cannula had lower quality of life in the physical, social, and total domains than those in the speaking valve group (poor QoL in the physical domain: 66.67% vs. 9.52%; social domain: 85.71% vs. 57.14%; total domain: 76.19% vs. 4.76%; p<0.001). From the multivariate analysis, the tracheal cannula type influenced the patient's quality of life was (p<0.001). The probability of someone with a fenestrated tracheal cannula will experience a poor QoL is 76.2%, while speaking valve is 4.7%. Conclusion: The quality of life of patients with a fenestrated type of tracheal cannula is significantly lower than that of speaking valve tracheal cannula users in both the physical, social, and total domains as measured by the V-RQOL.